Analysis of E-learning user Acceptance using the Technology Acceptance Model (TAM) and end-User Computing Satisfaction (EUCS) - Nur Alamsyah; Budiman; Titan Parama (Formosa Journal of Applied Sciences, 2023)
This research aims to analyse the acceptance of E-Learning among students of Universitas Informatika dan Bisnis Indonesia by using Technology Acceptance Model (TAM) and End-User Computing Satisfaction (EUCS) approaches, which are often used by researchers to examine user acceptance and satisfaction with technology. The results of this study indicate that the influence between the variables Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, Content, Accuracy, Format, Timeliness, Ease and User Satisfaction obtained a total value of 29,140 and on the continuum line shows that it is in the Very Good category. The results in this study also prove that there are 6 (six) accepted hypotheses and 3 (three) hypotheses that are not accepted. This result can be used as a suggestion for E-Learning Universitas Informatika dan Bisnis Indonesia to evaluate shortcomings in user satisfaction, as well as maintaining existing quality.